Pooled outcomes of performing freehand transperineal prostate biopsy with the PrecisionPoint Transperineal Access System. Issue 6 (28th June 2022) - Tzeng, Michael; Basourakos, Spyridon P.; Patel, Hiten D.; Allaway, Matthew J.; Hu, Jim C.; Gorin, Michael A.
Abstract: Objectives: To report the results of a pooled analysis evaluating the cancer detection rates, complications, and tolerability of prostate biopsies performed using the PrecisionPoint Transperineal Access System. Patients and Methods: The medical literature was reviewed to identify studies published prior to 1 October 2021 evaluating the PrecisionPoint device for performance of transperineal prostate biopsy. Pooled analyses were performed to assess overall and clinically significant cancer detection rates. Additionally, data on complications as well as patient tolerability of the procedure when performed under local anaesthesia were extracted. Results: Transperineal biopsy with the PrecisionPoint Transperineal Access System achieved overall and clinically significant cancer detection rates of 67.9% and 42.6%, respectively. Among patients with Prostate Imaging Reporting and Data System 3, 4, and 5 lesions on prostate magnetic resonance imaging, clinically significant disease was found in 31.7%, 55.7%, and 71.8% of patients, respectively. Complications were rare, with sepsis reported in 4 (0.1%) of 3411 procedures despite frequent omission of antibiotic prophylaxis. Patients reported acceptable tolerability of the procedure when performed under local anaesthesia. Conclusions: Within the available medical literature, there is uniform evidence supporting the use of the PrecisionPoint Transperineal Access System for performing prostate biopsy procedures. The reported cancer detection and infectious complication rates with this device are in line with other methods for performing transperineal prostate biopsy. A unique aspect of the PrecisionPoint device is its ability to facilitate performing transperineal prostate biopsy under local anaesthesia. This factor will likely lead to increased adoption of the beneficial transperineal approach to prostate biopsy.